P520Percutaneous coronary intervention for chronic total occlusions of coronary arteries: procedural characteristics and long-term clinical outcomes. (15th July 2014) - Jeremic, V; Stojkovic, S; Dobric, M; Vukcevic, V; Orlic, D; Cvorovic, I; Vasiljevic-Pokrajcic, Z
Abstract: Purpose: Despite the fact that techniques for recanalization of chronic total occlusions (CTO) are improved, the benefit of successful recanalization of the artery remains unclear. The aim of our study is to determine the success rate of percutaneous procedures and to evaluate the event free long-term survival in patients with CTO who underwent percutaneous coronary intervention (PCI). Methods: Our study included 283 consecutive patients with chronic total occlusions who underwent percutaneous coronary intervention on CTO at Clinic for Cardiology, between Jan 1st 2009 and Dec 31st 2010. Data were obtained retrospectively from Cath lab database at Clinic for Cardiology. Follow up data were obtained by direct phone contact. Results: Overall procedural success was achieved in 62.3% interventions. Independent predictors for procedural failure were presence of vessel tortuosity (P=0.007), vessel wall calcifications (P=0.000), blunt stump (P=0.000) and unstable angina pectoris as negative predictor (P=0.009). Overall MACE rates were similar in the procedural success and procedural failure groups (10% vs. 12.8%, p=0.455). There was no significant difference in the event free survival rate between success and failure group (89.8% vs. 87.2%, Log-Rank =0.468, p=0.494). Conclusions: Our study demonstrated that success rate of PCI in patients with CTO is acceptable and safe. Nevertheless, successful recanalization of CTO was not associated with an improved event free survival.